Penerapan Project Based Learning (PJBL) Untuk Meningkatkan Motivasi Belajar IPA: Cahaya - Dewi, Adelia Febi Kumala; Putri, Assaniatin Kartika; Puspitasari, Rima Eka; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In Implementation of project-based learning to increase motivation to learn science : Light uses a research and development approach because it aims to produce products such as learning media that can be used effectively in the learning environment. The techniques used in data collection are direct practice and library research. Data analysis includes three elements, namely: data reduction, data presentation, and conclusion drawing. In this article we invite readers to create project-based learning media that can be used as a tool to facilitate the delivery of messages and learning materials to be achieved. In its understanding, light is an electromagnetic emission that can be seen by the human eye by hitting an object and the object reflects into the human eye. The nature of light from the research conducted is that light can propagate straight: Light directed at a hollow object can propagate straight towards the screen, refracted: In objects that are put into water the submerged part shifts, reflected:Â When a flashlight is pointed at an object, the object's light is reflected back by the object, decomposed:Â When pointing the flashlight at the mica, we can see the light through the mica, through the clear object: When pointing a flashlight at a CD, decomposition occurs which is characterized by the appearance of a colorful spectrum of light like a rainbow.